1983
DOI: 10.1084/jem.157.6.1758
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nonlymphoid cells derived from rat peripheral lymph

Abstract: Mesenteric lymphadenectomy in rats is followed by union of peripheral and central lymphatics, allowing the collection of intestine-derived peripheral lymph cells via the thoracic duct for several days. These cells include a proportion of nonlymphoid cells (NLC) that show irregular and heterogeneous surface morphology including long pseudopodia and veils. They stain variably for nonspecific esterase and acid phosphatase and are ATPase-positive. Their nuclei are irregular and some contain cytoplasmic inclusions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
186
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(200 citation statements)
references
References 47 publications
13
186
1
Order By: Relevance
“…However, little is known about TLR expression on and responsiveness of migrating DC (and potential subsets thereof), as they cannot be studied easily in mice or humans. In this study we have examined these migrating intestinal DC directly in lymph using our unique model [23]. We extend our previous studies and show that DC migrating from the small intestine comprise three distinct subsets.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, little is known about TLR expression on and responsiveness of migrating DC (and potential subsets thereof), as they cannot be studied easily in mice or humans. In this study we have examined these migrating intestinal DC directly in lymph using our unique model [23]. We extend our previous studies and show that DC migrating from the small intestine comprise three distinct subsets.…”
Section: Discussionsupporting
confidence: 67%
“…Rats used were males 12-24 wks of age. Mesenteric and coeliac lymphadenectomy (MLNX and CoeLNX, respectively) and thoracic duct cannulation were performed as described previously [23,31]. All procedures were carried out in accordance with Home Office guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…CD11b + and CD11b -DC subsets are found in mice and rats as fixed subsets [9,12], and it was recently demonstrated that CD11b is not involved in the regulation of DC migration in rats [30]. Although Pugh et al [11] detected more DC in afferent lymph draining lengths of rat intestine with PP than of those without PP, this difference was not shown as significant, and DC were identified only by morphology in their study. Notably, even in lengths of gut containing PP, a large amount of tissue is normal LP.…”
Section: Discussionmentioning
confidence: 80%
“…However, it is still largely unknown where these antigenbearing cells originate from: Shreedhar et al claim that the major source of migrating DC in lymph is the LP [4], where DC can sample antigens from the gut lumen by extending dendrites into the epithelium [10]. Conversely, Pugh et al observed a larger number of DC in lymph draining from PP regions than in lymph draining from the normal LP [11]. In different compartments of the murine intestinal tract, phenotypically distinct DC subsets have been identified [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Here they initiate specific immune responses against the loaded antigens by presenting them in combination with costimulatory molecules to antigenspecific lymphocytes [5]. In non-inflamed tissues, DC have a turn-over time of several days to several weeks [6][7][8], requiring a constant replenishment of DC in the tissues by emigration of precursor/immature DC from the blood [9]. The molecules which are involved in this process of homeostatic extravasation of DC across resting endothelium remain ill-defined.…”
Section: Introductionmentioning
confidence: 99%